BODY IMAGE DAN SOCIAL COMPARISON DI ERA INSTAGRAM: STUDI KORELASI PADA EMERGING ADULTHOOD - Kharisma, Adhananda; Mukti, Patria; Nugroho, Yustinus Joko Dwi (Program Studi S1 Psikologi, 2024)
The development of information technology that attracts the interest of emerging adulthood is Instagram. Excessive use of Instagram allows the phenomenon of social comparison, it can affect body dissatisfaction, bring up negative moods, tend to make someone feel low self-esteem and make someone compare themselves with others, therefore social comparison can affect body image. This study aims to investigate the relationship between social comparison and body image among emerging adulthood Instagram users. The hypothesis proposed in this study is that social comparison will have a negative relationship with body image in emerging adulthood Instagram users. This study uses quantitative methods and sampling is done using proportional stratified random sampling technique. The subjects of this study were 329 emerging adulthood Instagram users at Universitas Setia Budi who were in the age range of 18-25 years. The data collection for the variables social comparison and body image was conducted using a likert scale questionnaire. The data analysis method used was Karl Pearson's product moment correlation using SPSS 25.0 for windows release. The results of the analysis showed a correlation coefficient of rxy = -0.790 with p = 0.000 (p <0.05). This proves that there is a significant negative relationship between social comparison and body image and therefore the hypothesis proposed in this study is accepted. The Rsquare value of 0.624 means that social comparison has an effective contribution of 62,4% to body image, with other factors being influenced by self-esteem, self-schema theory, perception, development, socio-cultural, gender, age, interpersonal relationships, mass media and family.